Parent education and training for autism spectrum disorder: evaluating the evidence for implementation in low-resource environments - Dawson-Squibb, John-Joseph Saunders (Department of Psychiatry and Mental Health, 2018)
The World Health Organization has recognised Autism Spectrum Disorder (ASD) as a public health concern and have recommended access to appropriate assessment and interventions. Psychoeducation and parent support soon after diagnosis are considered global best practice. Parent Education & Training (PET) programmes provide education, skills and support to parents. Despite the high need for PET there has been limited research in this field and few programmes are available, particularly in low- and middle-income countries (LMIC). This project aimed to 1) evaluate the evidence-base for a UK-developed PET (EarlyBird/EarlyBird Plus); 2) evaluate the evidence-base for a broader range of PET; 3) generate a framework for evaluating global PET programmes; 4) conduct a comparative feasibility study of two PET programmes in South Africa. The EarlyBIrd/EarlyBird Plus scoping review identified a low level of evidence for the efficacy of the PET, and showed that relatively little implementation science examination of the programmes had been performed to date. Review of a broader range of PET showed very similar findings, suggesting that the field of PET (rather than any specific intervention) was still relatively immature. We proceeded to use an implementation science and participatory approach to generate a multi-stakeholder evaluation framework for PET in future studies. A mixed-methods quasi-experimental design was then used for a comparative feasibility study of two PET in a low-resource South African setting. In the feasibility study parents/carers found both programmes to be acceptable and adaptable for a South African context. Limited efficacy-testing showed positive outcomes for parents, children and families. Application of the Evaluation Framework proved to be a useful structural technique to identify the strengths and weaknesses of PET across the implementation themes of outcomes, processes & procedures, and implementation landscape. Taken together, our results highlighted the relative infancy of this important field of ASD research and identified the need for multi-site, randomized controlled trials of PET, particularly in low-resource settings. In addition, results underlined the importance not only of efficacy of programmes, but of a range of implementation-related factors, that are crucial to ensure sustainable and scalable PET in real-life settings around the globe.